Duration of Intracranial Pressure Increase after Aneurysmal Subarachnoid Hemorrhage: Prognostic Factors and Association with the Outcome - Ketelauri, Pikria; Gümüs, Meltem; Gull, Hanah Hadice; Said, Maryam; Rauschenbach, Laurèl; Dinger, Thiemo Florin; Chihi, Mehdi; Oppong, Marvin Darkwah; Ahmadipour, Yahya; Dammann, Philipp; Wrede, Karsten Henning; Sure, Ulrich; et al. (Current Neurovascular Research, 2024)
ObjectiveA rupture of the intracranial aneurysm is frequently complicated, with an increase of intracranial pressure (ICP) requiring conservative and/or surgical treatment. We analyzed the risk factors related to the duration of pathologic ICP increase and the relationship between ICP burden and the outcome of subarachnoid hemorrhage (SAH).MethodsConsecutive cases with aneurysmal SAH treated at our institution between 01/2003 and 06/2016 were eligible for this study. Different admission variables were evaluated to predict the duration of ICP increase >20 mmHg in univariate and multivariate analyses. The association of the ICP course with SAH outcome parameters (risk of cerebral infarction, in-hospital mortality, and unfavorable outcome at 6 months defined as modified Rankin scale >3) was adjusted for major outcome-relevant confounders.ResultsOf 820 SAH patients, 378 individuals (46.1%) developed at least one ICP increase requiring conservative and/or surgical management after aneurysm treatment (mean duration: 1.76 days, range: 1 - 14 days). In the multivariable linear regression analysis, patients’ age (unstandardized coefficient [UC]=-0.02, p <0.0001), World Federation of Neurosurgical Societies (WFNS) grade 4-5 at admission (UC=0.71, p <0.004), regular medication with the angiotensin-converting enzyme (ACE) inhibitors (UC=-0.61, p =0.01), and presence of intracerebral hemorrhage (UC=0.59, p =0.002) were associated with the duration of ICP increase. In turn, patients with longer ICP elevations were at higher risk for cerebral infarction (adjusted odds ratio [aOR]=1.32 per-day-increase, p <0.0001), in-hospital mortality (aOR=1.30, p <0.0001) and unfavorable outcome (aOR=1.43, p <0.0001). SAH patients who underwent primary decompressive craniectomy (DC) showed shorter periods of ICP increase than patients with a secondary decompression (mean: 2.8 vs 4.9 days, p <0.0001).ConclusionThe duration of ICP increase after aneurysm rupture is a strong outcome predictor and is related to younger age and higher initial severity of SAH. Further analysis of the factors impacting the course of ICP after SAH is essential for the optimization of ICP management and outcome improvement.
Keywords: intracranial pressure increase